2022
DOI: 10.1002/wlb3.01026
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fine‐scale topography on detection of a mammal assemblage at camera traps in a mountainous landscape

Abstract: Changes in topography, such as terrain elevation and slope, are an important source of landscape complexity influencing the ecology of animals, particularly in mountainous landscapes. In such landscapes animals navigate changes in elevation and slope in their daily movement. Despite the importance of topographic variation, studies of animal ecology in mountainous landscapes tend not to explicitly consider those effects on species detection. We deployed a broad‐extent, coarse resolution camera‐trapping system a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Although we would not expect camera traps to decrease performance until -20°C or below (Reconyx, 2022), it is worth noting that other research has observed camera traps performing best around 0°C, where higher false-negatives occur in positive temperature ranges (Jacobs & Ausband, 2018), and negative temperature ranges and associated weather can contribute to decreased performance (Maile et al, 2023). Conducting jog-tests during other seasons and within a greater range of forest types and habitat will likely contribute to detecting statistical differences in environmental covariates and help determine if a cameras ECA varies more substantially across space and time (e.g., as in McIntyre et al, 2020; Moeller et al, 2023; Moll et al, 2020; Sultaire et al, 2023; Urbanek et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we would not expect camera traps to decrease performance until -20°C or below (Reconyx, 2022), it is worth noting that other research has observed camera traps performing best around 0°C, where higher false-negatives occur in positive temperature ranges (Jacobs & Ausband, 2018), and negative temperature ranges and associated weather can contribute to decreased performance (Maile et al, 2023). Conducting jog-tests during other seasons and within a greater range of forest types and habitat will likely contribute to detecting statistical differences in environmental covariates and help determine if a cameras ECA varies more substantially across space and time (e.g., as in McIntyre et al, 2020; Moeller et al, 2023; Moll et al, 2020; Sultaire et al, 2023; Urbanek et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although vegetation cover in our study had a relatively lower influence on ECA (Table 2, Figure 6), the importance of different predictor variables, will likely depend on the geography and habitat conditions of the study. For example, topography (Sultaire et al, 2023) and weather (Madsen et al, 2020) have been found to influence camera trap capture probabilities in some geographies. Thus, if implementing our method, researchers should consider all potential important predictor variables that may influence capture probability at their study sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As ecosystems and species shift their distributions to track changing climates, sharp topographic constraints and bottlenecks from human‐induced habitat fragmentation will decrease species’ abilities to persist and adapt. High physiographic and habitat diversity in mountains also amplifies the inadequacy of spatial prioritization and planning for use with relatively coarse analytical units, like ecoregions (e.g., Dinerstein et al., 2017), because they fail to capture critical features, such as landforms characteristic of mountains (Sultaire et al., 2022).…”
Section: Introductionmentioning
confidence: 99%